Real-time Relevance: RAG with Dynamic Context for Improved Natural Language Responses - Landgren, Malte; Giljegård, Oskar (My University, 2024)
Today’s Retrieval Augmented Generation (RAG) systems often struggle when trying to answer questions that require complex multi-hop reasoning. In this thesis we investigate an autoregressive Large Language Model (LLM) architecture which can generate a real-time relevant dense search vector for every token generation step. To facilitate this we also develop a synthetic data generation technique to acquire search query vector labels on a token-by-token level, requiring only a generating LLM and a document database. We investigate the quality of the synthetic data, and provide an attention based relabeling method which decreases hallucinations, improving the correctness of the labels by 67%. The architecture is able to produce query vectors 27 times faster than a separate embedder at the cost of retrieval accuracy. Finally, we train and employ the model in an active retrieval question-answering setting.
Keywords: LLM; RAG; active retrieval; synthetic data generation; master thesis